PENGARUH GAYA KEPEMIMPINAN KHARISMATIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI SURABAYA INTERCULTURAL SCHOOL - Andrew Andrean Frasta; Suryati Eko Putro; Novie Noordiana R. Y (JURASIMA, 2024)
This study aims to determine the effect of charismatic leadership style and work discipline on employee performance at Surabaya Intercultural School. This study is a descriptive study using a quantitative approach. The sample in this study amounted to 37 people. The instruments used have passed the validity and reliability test stages. Data collection through observation, questionnaires and interviews. While data analysis was carried out using multiple regression analysis, coefficient of determination and hypothesis testing using the t test. The results of the study using a probability level or significance level of 0.05 showed that charismatic leadership style has a significant effect on employee performance as indicated by the calculated t value> t table (2.704> 2.032). Work discipline has a significant effect on employee performance as indicated by the calculated t value> t table (2.852> 2.032). From the results of this study, it can be said that the work discipline variable (X2) is the most dominant variable in influencing employee performance at Surabaya Intercultural School. This is suspected that employees at Surabaya Intercultural School have good work ethics. This is also supported by the success of leaders in providing good examples at work. The success of leaders in carrying out their managerial functions makes employees feel like they are part of the big family of Surabaya Intercultural School.